2009
DOI: 10.1007/978-3-642-01009-5_4
|View full text |Cite
|
Sign up to set email alerts
|

A New Binary Description of the Blocks Relocation Problem and Benefits in a Look Ahead Heuristic

Abstract: Abstract. We discuss the blocks relocation problem (BRP), a specific problem in storing and handling of uniform blocks like containers. The BRP arises as an important subproblem of major logistic processes, like container handling on ships or bays, or storing of palettes in a stacking area. Any solution method for the BRP has to work with the stacking area and needs to draw relevant information from there. The strength of related approaches may rely on the extensive search of neighborhood structures. For an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 12 publications
0
43
0
Order By: Relevance
“…Experimental results showed that the model-based heuristics were competitive for both static and dynamic problems. Caserta et al (2009) developed a binary description of the bay configuration to adapt heuristics and metaheuristics, and used the new description within a look ahead heuristic to solve the static reshuffling problem. proposed a new metaheuristic approach based on dynamic programming for the static reshuffling problem.…”
Section: .Literature Reviewmentioning
confidence: 99%
“…Experimental results showed that the model-based heuristics were competitive for both static and dynamic problems. Caserta et al (2009) developed a binary description of the bay configuration to adapt heuristics and metaheuristics, and used the new description within a look ahead heuristic to solve the static reshuffling problem. proposed a new metaheuristic approach based on dynamic programming for the static reshuffling problem.…”
Section: .Literature Reviewmentioning
confidence: 99%
“…Since the quality of the solution depends on the length and height of the corridor, in two later papers, Caserta and Voß (2009a) and Caserta and Voß (2009c) incorporate heuristic algorithms to tune these variables. Caserta et al (2009) propose a greedy heuristic algorithm to solve the BRP. In their heuristic, a reshuffled container will be stacked either in a pile which is empty or in a pile of containers that have lower retrieval priority.…”
Section: Minimizing Container Reshufflingmentioning
confidence: 99%
“…Consequently, a number of references dealing with this type of problem can be found under the captions "minimizing the number of rehandling operations," e.g. Caserta et al (2009a), Caserta et al (2009c), and Kim and Hong (2006) or, alternatively, "minimizing rehandling time," e.g. Choe et al (2009), Kang et al (2006b), .…”
Section: Introductionmentioning
confidence: 99%